Effects of 4 multitargeted receptor tyrosine kinase inhibitors on regional hemodynamics in conscious, freely moving rats - Carter, Joanne J.; Fretwell, Laurice; Woolard, Jeanette (Federation of American Society of Experimental Biology, 2016)
VEGF inhibitors, including receptor tyrosine kinase inhibitors, are used as adjunct therapies in a number of cancer treatments. An emerging issue with these drugs is that most cause hypertension. To gain insight into the physiological mechanisms involved, we evaluated their regional hemodynamic effects in conscious rats. Male Sprague Dawley rats (350–450 g) were chronically implanted with pulsed Doppler flow probes (renal and mesenteric arteries, and the descending abdominal aorta) and catheters (jugular vein, peritoneal cavity, and distal abdominal aorta). Regional hemodynamics were measured over 4 d, before and after daily administration of cediranib (3 and 6 mg/kg, 3 and 6 mg/kg/h for 1 h, i.v.), sorafenib (10 and 20 mg/kg, 10 and 20 mg kg/h for 1 h, i.v.), pazopanib (30 and100 mg/kg, i.p.), or vandetanib (12.5 and 25 mg/kg, i.p.). All drugs evoked significant increases (P < 0.05; n = 7–8) in mean arterial pressure, which were generally accompanied by significant mesenteric and hindquarters, but not renal, vasoconstrictions. The hypertensive effects of cediranib were unaffected by losartan (10 mg/kg/h), bosentan (20 mg/kg/h), or a combination of phentolamine and propranolol (each 1 mg/kg/h), suggesting a need for new strategies to overcome them.—Carter, J. J., Fretwell, L. V., Woolard, J. Effects of 4 multitargeted receptor tyrosine kinase inhibitors on regional hemodynamics in conscious, freely moving rats.